(untitled) (Western European Journal of Medicine and Medical Science, 2025)
This article analyzes the application of blockchain technology in medicine and its role in ensuring data security. The advantages of a blockchain such as data non-corruption, permission-based access, and transparency are considered. The results of the study show that, in addition to ensuring an effective exchange of information in the field of blockchain medicine, its implementation can also face legal and technical difficulties.